Implementasi Kebijakan E-Retribusi Pasar Tradisional Dalam Rangka Pencegahan Kebocoran Pendapatan Asli Daerah Di Kabupaten Tabanan - I Putu Adhi Suryanata; Hendra Felani (JEKP (Jurnal Ekonomi dan Keuangan Publik), 2023)
ABSTRACT This study focuses on problems related to the collection of retribution for traditional markets which are often bogus, causing the local revenue in Tabanan Regency to be less than optimal. This study aims to explain the process of implementing the traditional market e-retribution policy to prevent leakage of local revenue in Tabanan Regency. The research method used is a qualitative research with a descriptive approach. Data collection techniques using interviews, observation, and documentation. The results of this study indicate that the presence of e-retribution in traditional markets is very influential on increasing local revenue in Tabanan Regency, which can be seen from the comparison of regional original income before the use of e-retribution and after the use of e-retribution in traditional markets. The data shows that there is a significant increase in income from the traditional market retribution sector after the implementation of the e-retribution program at traditional markets in Tabanan Regency. Barriers to the implementation of e-retribution are constrained by human resources and are also related to operations in traditional markets, so that not all traders are provided with a QR code scan tool for the implementation of this e-retribution. Keywords: Policy Implementation, Traditional Markets, Local Revenue